Cultural Diversity at Work: The Effects of Diversity Perspectives on Work Group Processes and Outcomes - Ely, Robin J.; Thomas, David A. (Administrative Science Quarterly, 2001)
This paper develops theory about the conditions under which cultural diversity enhances or detracts from work group functioning. From qualitative research in three culturally diverse organizations, we identified three different perspectives on workforce diversity: the integration-and-learning perspective, the access-and-legitimacy perspective, and the discrimination-and-fairness perspective. The perspective on diversity a work group held influenced how people expressed and managed tensions related to diversity, whether those who had been traditionally underrepresented in the organization felt respected and valued by their colleagues, and how people interpreted the meaning of their racial identity at work. These, in turn, had implications for how well the work group and its members functioned. All three perspectives on diversity had been successful in motivating managers to diversify their staffs, but only the integration-and-learning perspective provided the rationale and guidance needed to achieve sustained benefits from diversity. By identifying the conditions that intervene between the demographic composition of a work group and its functioning, our research helps to explain mixed results on the relationship between cultural diversity and work group outcomes.